Diabetes Distress: Assessment And Screening Of Stress Levels Among People With Diabetes Mellitus - Asbath Said; Mikawati Mikawati; Waode Rahmadania; Ahmad Mudatsir (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Type 2 diabetes mellitus patients are more likely to suffer from depression, with a prevalence of between 24% and 29%. In 2017, there were 184 people with diabetes in the Poasia Health Center's working area, but only 26 of them were actively participating in the prolanis program on a regular basis. The low number of patients who are actively seeking treatment is likely due in part to the fact that they have diabetes. Methods: Patients with diabetes mellitus (DM) who are registered as prolanis patients at the Poasia Kendari health center are the focus of this descriptive study. Depression levels were assessed using the Diabetes Distress Scale (DDS 17). Results: There were 26 patients with type II diabetes mellitus (also known as "type II diabetes mellitus") who participated in the researcher's study based on demographic data obtained from the Poasia Health Center that were diagnosed with mild depression, with as many as 20 of them falling into this category. (76.22%), while 23% to 24% of respondents (23.08%) were suffering from moderate to severe depression